Upaya Pemerintah Menangkal Gerakan Radikalisme - Siregar, Bahtiar; Ependi, Rustam (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2021)
Radicalism itself is an understanding of the thoughts of a group of people who want renewal for a better life but in a way that is not right because it justifies all means. More and more movements are emerging because of religious, political, and other issues. Most forms of radicalism are actions that are negative for the public. Democracy is supposed to make society more fluid, egalitarian and inclusive, but the opposite is happening. However, it is undeniable that radicalism can easily enter Indonesia, as previously explained. For this reason, the government has prepared various efforts to overcome radicalism in Indonesia. Police agencies, for example, prepare special forces to eradicate radicalism in Indonesia.